Mental preparation of karateka for sports competition in kata - Piepiora, Paweł Adam; Jurczyk, Julia Barbara; Vveinhardt, Jolita (Frontiers in Sports and Active Living, 2025)
Mental preparation for sports competition in karate is significant, as it is deeply embedded in the philosophical and ethical values that underpin this combat method. In practice, the mental preparation of karateka varies depending on the type of competition, for example preparation for kata (forms) and kumite (fights). Thus, this perspective offers a concise account of the authors' viewpoint on the leading mental skills required of kata competitors. It is argued that self-esteem, inner speech, imagination, visualisation, values and personality play a significant role in the development of confidence. In addressing stress, attention was directed towards the role of arousal, coping strategies, Jacobson's progressive relaxation, Schultz's autogenic training, biofeedback, schemas and scripts. Effective management of anxiety relies on the utilisation of mindfulness and desensitisation techniques. In maintaining attention, effective attention management, attention styles, the ability to filter out distractions, mantras and affirmations are significant. Conversely, practicing tasks that induce a Stroop effect can improve executive function skills. The above elements of mental preparation for kata competitors are universally applicable to all competitors in this field, yet they are not the sole elements that may be employed. Given the individual predispositions of kata competitors, other mental training techniques may also be applicable.